MORNING AND EVENING MADRASAS OF DISTRICT THIRUVANANTHAPURAM OF KERALA : A CASE STUDY - Jaireth, Sushma; S, Shiraz (THE PRIMARY TEACHER, 2010)
In Muslim community, religious education is a means of acquiring values, norms, a meaning of life, a purpose of social relationship and identity. Primary level Madrasa education helps children to develop personality and better understanding of their religious faith. The connotation of the term Madrasa in Kerala is different from its North Indian counterparts. In North, Islamic education is generally called Maktab or Madrasa education. Maktab stands for the centres imparting basic religious knowledge and Madrasas for higher Islamic learning or religious seminars. In south, especially in Kerala, the term Madrasa is used to explain the institutions providing basic religious knowledge and the terms Arabic/ Islamiya colleges and Jamias used for higher Islamic learning centres.